Geochemistry of Sulphides from Papua New Guinea: Golpu and Nambonga North Porphyry Cu-Au Deposits, Wafi-Golpu Mineral District - Moira Lunge; Joseph O. Espi (Current Advances in Geography, Environment and Earth Science Vol. 1, 2021)
Studying elemental geochemistry of hypogene sulphides can discriminate the hydrothermal fluids responsible for ore formation. To determine whether Golpu porphyry Cu-Au deposits are related to the Nambonga North porphyry system which is located 2.5 km apart in the Wafi-Golpu Mineral District, Papua New Guinea, we compare the trace element compositions of drill core chalcopyrites and pyrites analysed using Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICPMS). Although mineralisation also occurs in other mineral phases such as enargite, covellite, tennantite, pyrite and chalcopyrite are quite distinct, making them easier to work on in this study. The results for the Golpu chalcopyrites revealed high concentrations of Au, As, Se, Mo, Sb, Te and Bi and lower concentrations of Ag and Zn compared to those from Nambonga. Pd and Pt were below the detection limit in chalcopyrites for both deposits. The results for the Golpu pyrites indicated high concentrations of Pt, Au, Se, Mo, Sb, and Te and lower concentrations of Cu, Zn, As, Ag, Pb, Pd and Bi compared to those from Nambonga North. Au concentrations in the pyrites from both the porphyry deposits were higher compared to chalcopyrites, which mean that pyrite is the Au-bearing sulphide responsible for the higher Au content. In contrast, Cu values in pyrites from Nambonga North are higher than those from Golpu. Overall, it is envisaged that the ore fluids were exsolved at different times during the evolution of both porphyry deposits, although these porphyry centres may be related in space and time.